Gastric polypoid intramucosal carcinoma and an adjacently located leiomyoma at the cardia - Arzu ÇELEBİ KOBAK; Müjdat ZEYBEL; Semin AYHAN; Ahmet AYDIN; Yavuz KAYA; Ender ELLİDOKUZ (Turkish Journal of Gastroenterology, 2019)
-